Community share ownership trust/schemes as a viable option for local economic development in Zimbabwe: the case of Lupane District Community Share Ownership Trust/Scheme - Ndlovu, Million (Midlands State University, 2015)
The research analyses the Community Share Ownership Trust/ Schemes (CSOTS) as viable option for Local Economic Development in Zimbabwe. Despite boasting of the abundance of natural resources ranging from the large methane gas reserves deposits, timber, coal and wild life, the Lupane community has been deprived of the benefits realised from these resources hence the district has remained impoverished resulting in lack of development. The study used both qualitative and quantitative methods to collect data. The research gives an indication of how the community of Lupane district can effectively and efficiently utilize the CSOTS to empower the communities in order to stimulate Local Economic Development. The strategies for Local Economic Development in general as well as the conceptual framework of CSOTS, which are major strategies currently adopted by the Government of Zimbabwe as empowerment models for local communities were evaluated. The findings of the study indicated that the CSOTS are pro-poor empowerment policies that can lead to sustainable human development as well as eradication of poverty. It was also found that the level of awareness and participation of the communities were low hence there was need for the Lupane District leadership to have a deliberate effort of creating awareness and ensure effective participation by communities in the CSOTS. The study also noted that companies exploiting resources had pledges that they did not honour due to the absence of an enforcement mechanism which compels these companies to honour the pledges within a specified timeframe. Consequently, the study found that the CSOTS had not been funded three years after companies had made pledges hence no meaningful development had been realised in Lupane district. The study concluded that with adequate funding, integrated development plan, sound management of the trust and effective participation of all stakeholders, the CSOTS is a viable option for Local Economic Development. The study recommends that the government develops a legal instrument which ensures compliance on the part of companies exploiting recourses in the district to honour their pledges within a stipulated timeframe to ensure that CSOTS’ set goals and objectives of ensuring Local Economic Development and sustainable human development are realised.